2021
DOI: 10.29303/jipp.v6i3.275
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Interaktif Berbasis Macromedia Flash Sebagai Bentuk Penguatan Keterampilan Membaca Siswa Kelas II Sekolah Dasar

Abstract: Penelitian ini bertujuan untuk mengembangkan dan mengetahui kelayakan media interaktif berbasis macromedia flash sebagai bentuk penguatan keterampilan membaca siswa kelas II sekolah dasar serta untuk mengetahui keefektifan produk hasil pengembangan media interaktif berbasis macromedia flash. Jenis penelitian ini adalah R & D (Research and Development) dengan model Alessi & Trollip. Metode pengumpulan data menggunakan angket atau kuesioner, dokumentasi dan tes. Jenis data yang digunakan adalah data kual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…A number of studies related to the above phenomenon have been carried out before, among others, to improve the reading skills of low grade students (Kuncoro Adi Saputro, Christina Kartika Sari, 2021;Made Sumantri1, Dewa Nyoman Sudana, 2017;Pramesti, 2015;Reni, 2022;Sri, 2019;Suci et al, 2021). In addition, other studies have revealed the effectiveness of beginning reading skills in grade students (Indah Nur Fitriana, Muhammad Tahir, 2021) (MetyToding, 2022). Other research has revealed the factors that cause students' low reading competence (Putri, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies related to the above phenomenon have been carried out before, among others, to improve the reading skills of low grade students (Kuncoro Adi Saputro, Christina Kartika Sari, 2021;Made Sumantri1, Dewa Nyoman Sudana, 2017;Pramesti, 2015;Reni, 2022;Sri, 2019;Suci et al, 2021). In addition, other studies have revealed the effectiveness of beginning reading skills in grade students (Indah Nur Fitriana, Muhammad Tahir, 2021) (MetyToding, 2022). Other research has revealed the factors that cause students' low reading competence (Putri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…And other research reveals a relationship between students' reading and writing skills (Agustin Rinawati, Lilik Binti Mirnawati, 2020). The methods often used in related research are qualitative (Agustin Rinawati, Lilik Binti Mirnawati, 2020;Indah Nur Fitriana, Muhammad Tahir, 2021;Made Sumantri1, Dewa Nyoman Sudana, 2017;Putri, 2020), Classroom Action Research (Kuncoro Adi Saputro , Christina Kartika Sari, 2021;Made Sumantri1, Dewa Nyoman Sudana, 2017;Pramesti, 2015;Reni, 2022;Suci et al, 2021), descriptive qualitative (MetyToding, 2022;Sri, 2019) Based on the illustration of the phenomenon and a number of related studies, the researcher is interested in revealing an increase in low grade students' reading activities by using the silaba method (iqra) in grade 1 students at SDN Banjarsari 01. This study aims to analyze the Silaba Method in Class 1 Beginning Reading Activities at Public Elementary Schools Bansari 01.…”
Section: Introductionmentioning
confidence: 99%
“…Secara sederhana dapat dikatakan bahwa banyak ditemukan anak yang membaca dengan terbata-bata (Santi, Barr, Khalaf, & Francis, 2015;Wahyuning, 2015;Yildirim & Rasinski, 2014). Proses pembelajaran membaca hanya terhenti pada kelancaran membaca yang melihat anak terbata-bata atau tidak (Protopapas, Katopodi, Altani, & Georgiou, 2018;Rahman, Sakti, Widya, & Yugafiati, 2019;Trisdania, 2018;Yulianeta, Damaianti, Amandangi, & Rahesi, 2020). Sebagian besar anak masih berada pada posisi mengenali kode dan masih sedikit anak yang sudah memahami makna teks yang dibaca (McCoach & Yu, 2015;Paige & Magpuri-Lavell, 2014;Taufina & Chandra, 2017a).…”
unclassified

Metode Hypnoteaching Meningkatkan Keterampilan Membaca Siswa Sekolah Dasar

Ni Luh Putu Libriana Lisna Dewara,
Desak Putu Parmiti,
Putu Nanci Riastini
2024
JEAR